New dimensions of Ediacaran Magmatism in the southeastern New England Avalon zone, USA - Thompson, Margaret D.; Crowley, James L.; Ramezani, Jahandar (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
High precision CA-ID-TIMS U-Pb zircon dates presented here establish 627.68 ± 0.66 Ma (2s internal uncertainty) Diorite at Rowley and associated granite near Topsfield, Massachusetts as the earliest arc-related magmatic rocks recognized so far in the Southeastern New England Avalon Zone. Granite dated at 609.10 ± 0.18 Ma on the southern extremity of this terrane in Newport, Rhode Island corresponds in age to previously dated Dedham Granite that is widespread in the vicinity of Boston, Massachusetts. Slightly younger diorite (605.48 ± 0.21 Ma) in an upfaulted block west of Boston clusters with previous dates from the Milford and Fall River granites, and Westwood Granite re-dated at 595.17 ± 0.50 Ma proves to be co-eval with Lynn-Mattapan volcanic rocks. LA-ICPMS age spectra from the same samples (except Westwood Granite) also show inherited components. The Ediacaran crystallization ages for the southeastern New England suite overlap LA-ICPMs ages from numerous samples in the Nova Scotia's Cobequid and Antigonish Highlands. These ages both reinforce previous comparisons between these terranes and reveal patterns of incremental intrusion like those documented for continental arc-related plutons of the western United States. Mesoproterozoic and older inherited components in both cases reflect West Avalonian origins as a series of volcanic arcs developed on metasedimentary deposits that detached from the Timanide margin of Baltica. By the time <630 Ma Jeffers block tuffs and Topsfield Granite acquired Cryogenian xenocrysts, these terranes were drifting towards collision with Ganderia, precluding Baltica provenance for ~680-640 Ma zircon. The source of this inheritance remains unresolved.